Libraries and Information Services towards the Attainment of the UN Millennium Development Goals - Koopman, Sjoerd (IFLA Publications, 2008)
The United Nations Millennium declarations of 2002 set eight Millennium Development Goals (MDGs) to be achieved by 2015. The papers presented in this publication endeavour to address how libraries and information professionals in East, Central and Southern Africa seek to make themselves relevant to national development by asking themselves how libraries and information centres could contribute to the attainment of these MDGs.; Sjoerd Koopman, Co-ordinator of Professional Activities, IFLA Headquarters, The Hague, Netherlands; Benson Njobvu , President, Zambia Library Association, Zambia.; ""I recommend this volume for academic and public libraries and all readers interested in African libraries and information services and how they can work towards the attainment of the Millennium Development Goals.""Martha S. Speirs in: African Research and Documentation 111/2009